Effect of management influence on disclosure quality of accounting information - omid pourheidari; Aref Forughi (مطالعات تجربی حسابداری مالی, 2019)
Influence of managers, specifically CEOs which is used as a mean of control the output of accounting information, may lead to management of disclosure quality timeliness and present information quality aligned with management interests. The presented study goal is to examine influence of CEO on disclosure quality of accounting information in Tehran Stock Exchange Listed Companies. In this paper, CEO tenure, duality of CEO role and mandate of executive board were used to measure management power. To examine the proposed hypothesis in this study, General linear model has been used. The samples were collected from 122 of the Companies listed in the Tehran Stock Exchange Between 2010 to 2017. Findings suggest that timeliness of accounting data has a negative and meaningful relation with management power. Meanwhile there was no trace of a meaningful relation between disclosure quality of accounting information and capacity of reliability on such accounting data; and management power. Such findings indicate that while managers use their power to timeliness of disclosure of data along with their interests, they refuse to use this power to sabotage the capacity of reliability of accounting information.